(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
In the following comprehensive article, we will delve into the environmental conditions of the Aral Sea region, exploring the causes and consequences of its dramatic decline and the ongoing challenges faced by the local communities and the surrounding ecosystem. We will examine the historical context, the socio-economic impacts, and the environmental repercussions, shedding light on the complex web of factors that have contributed to the current state of affairs.